2018
DOI: 10.3390/nu10050572
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc Intake and Its Association with Metabolic Syndrome Indicators among Chinese Adults: An Analysis of the China Nutritional Transition Cohort Survey 2015

Abstract: The dietary zinc consumed in Chinese households has decreased over the past decade. However, the national dietary zinc intake in the last five years has seldom been investigated. Using data from 12,028 participants 18 to 64 years old (52.9% male) in the China Nutritional Transition Cohort Survey (CNTCS) 2015, we describe the intake of dietary zinc and the contributions of major foods and we examine the relationship between the level of dietary zinc intake and metabolic syndrome indicators, including blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
5
16
0
Order By: Relevance
“…Consistent with findings in other studies [80,81], the unadjusted model revealed that Zn intake was associated with reduced SBP, indicating its deficiency as a risk factor for the occurrence of high BP. In contrast, other studies have reported that dietary intake of Zn does not affect BP in animals and humans.…”
Section: Relationship Between Dietary Micronutrient Intake and Cardiosupporting
confidence: 90%
“…Consistent with findings in other studies [80,81], the unadjusted model revealed that Zn intake was associated with reduced SBP, indicating its deficiency as a risk factor for the occurrence of high BP. In contrast, other studies have reported that dietary intake of Zn does not affect BP in animals and humans.…”
Section: Relationship Between Dietary Micronutrient Intake and Cardiosupporting
confidence: 90%
“…Zinc intake is related with development and progression of several chronic metabolic diseases [29e31]. In particular, a close association between insulin resistance and blood pressure has been repeatedly reported [17,20,32]. In a cross-sectional study of 3575 Indian participants, low zinc intake was associated with higher prevalence of coronary artery disease, diabetes, and altered metabolic surrogate markers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary zinc supplementation has shown beneficial roles in patients with chronic metabolic diseases [19]. Similarly, adequate zinc consumption is associated with reduced blood pressure and glucose control in Chinese diabetes and CVD patients [20]. Collectively, these results suggest a close relationship between zinc intake and metabolic and cardiovascular equanimity.…”
Section: Introductionmentioning
confidence: 90%
“…Further details of the CHNS can be found in previous publications [23][24][25]. Compared to previous survey rounds [23,24], an additional three provinces were included in 2015 [25]. All subjects gave their informed consent for inclusion before they participated in the study.…”
Section: Study Populationmentioning
confidence: 99%